Attitudes about collective bargaining in a non-bargaining state - Joseph A. Sarthory; Jerry Kinnaird (Educational Considerations, 1979)
Arkansas law requires that teachers be involved in the development of personnel policies and some districts utilize negotiations as a mechanism to satisfy this requirement.